Modified Slotted Patch Antenna with Metasurface as Superstrate for Dual-Band Applications - Samantaray D.; Ghosh S.K.; Bhattacharyya S. (My University, 2025)
This letter presents the design, circuit model analysis, and realization of a novel metasurface-based low-profile slotted patch antenna for dual-band applications in the C and X-bands. The antenna prototype comprises a modified slotted patch and a 7×7 array of periodic metasurface (MS) as superstrate configuration. Both the radiating patch and the MS layer have been designed over FR4 dielectric substrate while the overall dimension of the proposed antenna being 1.03λ0×1.03λ0×0.15λ0 only, where λ0 is the free-space wavelength at 8.62 GHz. The -10 dB impedance bandwidth of the proposed antenna has been realized at two distinct frequency bands ranging from 4.18 to 4.44 GHz and 8.11 to 11.14 GHz. The fractional bandwidths of 6.1% and 35.15% have been achieved at 4.26 and 8.62 GHz, respectively. The equivalent circuit model of the proposed prototype has been sequentially developed to validate the electromagnetic simulated results. The antenna radiates in the boresight direction, with a maximum realized gain of 8.72 dBi at 10.99 GHz and radiation efficiency of 91%. The proposed prototype has also been fabricated and the experimentally measured results are in good resemblance with the simulated one. © 2002-2011 IEEE.